EFFECTIVENESS OF E-BOOK APPLICATION MODEL UTERINE ATONY MANAGEMENT GUIDE AND POCKETBOOK IN IMPROVING MIDWIFE KNOWLEDGE AND SKILLS IN BASIC CARE: PRE-POST STUDY - Titik Hindriati; Nuraidah; Rosmaria; Diniyati (OPI Napoli, 2022)
Background: Midwives are one of the main health workers at the frontline of health development to accelerate the decline in Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Therefore, competent and skilled midwives are needed in carrying out clinical procedures, especially in handling emergency cases of postpartum hemorrhage, with critical analysis skills. This study aims to determine the effectiveness of e-book application model uterine hypotonia management guide and pocket book in improving midwife knowledge and skills in basic care. Method: The research design used was pre-post study, which was carried out in February-April 2021. The population and sample in this study were all midwives who provided delivery assistance at the Jambi City Health Center, totaling 64 respondents. Data analysis used the Wilcoxon and Mann-Whitney tests. Results: In each intervention group, all variables, including knowledge and skills, are increased in both groups defined. The results showed that the educational media application of guidelines and pocketbooks on postnatal emergency management increased knowledge and skills. Conclusion: The two study groups had a significant effect on increasing the knowledge and skills of midwives in handling postnatal emergencies due to uterine atony.